2020
DOI: 10.1007/s11783-020-1373-3
|View full text |Cite
|
Sign up to set email alerts
|

Application of Fe(VI) in abating contaminants in water: State of art and knowledge gaps

Abstract: The past two decades have witnessed the rapid development and wide application of Fe(VI) in the field of water de-contamination because of its environmentally benign character. Fe(VI) has been mainly applied as a highly efficient oxidant/disinfectant for the selective elimination of contaminants. The in situ generated iron(III) (hydr)oxides with the function of adsorption/coagulation can further increase the removal of contaminants by Fe(VI) in some cases. Because of the limitations of Fe(VI) per se, various m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
41
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 59 publications
(48 citation statements)
references
References 140 publications
(242 reference statements)
0
41
0
Order By: Relevance
“…These findings have profound implication in Fe­(VI) technologies for mitigation of EOCs in water and wastewater industries. Given that Fe­(V) and Fe­(IV) are much more reactive than Fe­(VI), ,, the generation of more Fe­(V) and Fe­(IV) from Fe­(VI) is one of the promising approaches for more efficient destruction of EOCs in Fe­(VI) applications. If the in situ production of Fe­(V) and Fe­(IV) can be well harnessed, better EOCs removals and lower Fe­(VI) dosages are expected in practices for improving the efficiency of Fe­(VI) treatment and saving the operation costs associated with water treatment.…”
Section: Environmental Implicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…These findings have profound implication in Fe­(VI) technologies for mitigation of EOCs in water and wastewater industries. Given that Fe­(V) and Fe­(IV) are much more reactive than Fe­(VI), ,, the generation of more Fe­(V) and Fe­(IV) from Fe­(VI) is one of the promising approaches for more efficient destruction of EOCs in Fe­(VI) applications. If the in situ production of Fe­(V) and Fe­(IV) can be well harnessed, better EOCs removals and lower Fe­(VI) dosages are expected in practices for improving the efficiency of Fe­(VI) treatment and saving the operation costs associated with water treatment.…”
Section: Environmental Implicationsmentioning
confidence: 99%
“…It was well documented that Fe­(V) and Fe­(IV) are 2–6 orders of magnitude more reactive than Fe­(VI), and the difference between the reactivity of Fe­(IV)/Fe­(V) and Fe­(VI) toward a specific EOC heavily relies on the species of EOCs under specific experimental conditions. , Moreover, solution chemistry and operating parameters can influence the difference extent in their reactivity toward a specific EOC. Although our previous work demonstrated the involvement of Fe­(V) and Fe­(IV) in the oxidation of the target EOC by Fe­(VI), the contributions of Fe­(V) and Fe­(IV) during EOCs oxidation by Fe­(VI) under different experimental conditions were not systemically assessed.…”
Section: Introductionmentioning
confidence: 99%
“…In an effort to identify toxic products which resulted from treating PPCP (pharmaceuticals and personal care products) wastes, Barisci & Dimoglo [163] described the mechanistic pathways of the reactions between ferrate(VI) and antibiotics, analgesics, β-blockers, lipid regulators, anti-psychotics and cytostatic drugs in detail, a rarity in the literature of wastewater science. This area of knowledge should be added to the "gaps" highlighted by Professor Guan Xiahong (Tonji University, Shanghai, China) and colleagues from various institutes (2021) in their review of ferrate(VI) [164].…”
Section: Investigation Of Components Of Iron Oxide-hydroxide Sludges As Part Of the Researchmentioning
confidence: 99%
“…The green oxidant, e.g., H 2 O 2 , potassium peroxysulfate (2KHSO 5 × KHSO 4 × K 2 SO 4 ), potassium persulfate (K 2 S 2 O 8 ), and ozone (O 3 ), is added in order to promote oxidation of organic compounds in landfill leachate (Anglada et al, 2011;Rivas et al, 2005;Xu et al, 2012;Zhai et al, 2016). Potassium ferrate(VI) is an emerging green water treatment agent frequently proposed for wastewater treatment (Wang et al, 2021). The results of recent study has shown that potassium ferrate(VI) can be successfully applied also for treatment of landfill leachate (Thomas et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…The results of recent study has shown that potassium ferrate(VI) can be successfully applied also for treatment of landfill leachate (Thomas et al, 2020). Potassium ferrate(VI) may oxidize organic compounds by electron or/and oxygen transfer mechanisms (Rush & Bielski, 1989;Chen et al, 2018;Luo et al, 2020aLuo et al, , 2020bWang et al, 2021). Thus, reactivity of potassium ferrate(VI) depends on pH value.…”
Section: Introductionmentioning
confidence: 99%